Practicing Cooperative Learning Model Using Picture Cube and Story Marker to Improve Writing Skills - Tisyrinul Awwal Fatiani; Arif Rahman; Jupri Jupri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
Cooperative learning provides various activities in the form of individual and group works in teaching language skills. This research aims to improve the writing skills ability using cooperative learning model. This study was action research. The research was conducted in one cycle following the cyclical action research model consisting of planning, acting, observing, and reflecting. The subjects of this research were 20 students in Class 8D. In this research, there was two types of data, it is qualitative and quantitative data. The qualitative data are analyzed following three stages of qualitative data analysis, namely data collection, data condensation, data display, conclusion drawing, and final reporting. Meanwhile, the quantitative data cover students’ writing achievement collected using writing tests. The findings of this research show that the students’ writing skills are improved. They mastered key vocabulary and grammatical knowledge to compose sentences. The students kept on using writing strategies through cooperative learning model to understand a given text. The teaching and learning activities were interesting. Media used are Picture Cube and Story Marker to support cooperative learning activities. It is elaborated in discussion part of this article.